INTRODUCTION TO "SPECIAL ISSUE ON THE EMPIRICAL ANALYSIS OF BUSINESS CYCLES, FINANCIAL MARKETS, AND INFLATION: ESSAYS IN HONOR OF CHARLES NELSON". (16th December 2013) - Kim, Chang-Jin; Morley, James; Piger, Jeremy; Kim, Chang-Jin; Morley, James; Piger, Jeremy
<x content-type="archive" xml:space="preserve">Abstract</x> Time series analysis of macroeconomic and financial variables requires a deep understanding of many econometric pitfalls if an empirical researcher hopes to avoid making spurious inferences. This understanding is the hallmark of Charles Nelson's research over four decades and it develops out of a healthy skepticism about "conventional wisdom, " yet a pragmatic belief that, despite the econometric hurdles, it is possible to learn from data. The papers in this special issue build on Charles Nelson's research legacy to address many important empirical questions related to business cycles, financial markets, and inflation, always with respect for the data, but wary of spurious inferences.